Vaccines in the modern world - Dougan, Gordon (Henry Stewart Talks, 2009)
What are vaccines?, Vaccine composition, Vaccines in common use, Type of immune response induced by vaccination, Impact on disease incidence, Smallpox: the first vaccine, Vaccines against polio and meningitis, What is a conjugated vaccine, Reverse vaccinology, Novartis MenB protein vaccine, Vaccines can now be based on DNA
Archived at 2020/01/15